Edukasi dan Implementasi Pola Hidup Bersih dan Sehat (PHBS) pada Siswa SD Negeri 1 Mertoyudan - Azkiya, Azza; Vadhilah, Mifta Ulva; Ardiyanti, Vivi (Lembaga Pengembangan Kinerja Dosen, 2026)
Clean and healthy living habits are an essential foundation in shaping a generation that is mindful of personal and environmental health. These habits need to be instilled from an early age, both at school and at home, so that they can become a sustainable part of students' lifestyles. This community service activity aims to improve the knowledge and skills of students at SD Negeri 1 Mertoyudan in consistently applying Clean and Healthy Living Behaviors (PHBS) in their daily lives. The implementation methods comprised three main approaches: interactive discussion-based education, a demonstration of proper handwashing techniques in accordance with WHO standards, and hands-on practice in maintaining personal hygiene. These approaches were chosen to ensure that students not only understand the concept of PHBS theoretically but are also able to apply it independently in real-life situations. The results of the activity showed a significant improvement in students' understanding of the importance of washing hands with soap at critical moments as a form of personal hygiene responsibility. Through a demonstrative approach that involved active student participation, participants were able to practice proper personal hygiene steps accurately and confidently. This activity is hoped to have a long-term impact in shaping students who are disciplined, responsible, and attentive to both personal and environmental health, while also serving as an effective preventive measure in reducing the risk of infectious diseases among school-age children.